To What Extent Business Excellence Dimensions Affect the Resilience and Performance of Qatari Enterprise: A Conceptual Report (Indian Journal of Management and Language (IJML), 2024)
An organization's performance can be led by implementing a management approach called "business excellence." However, the European Foundation for Quality Management (EFQM) and the Malcolm Baldrige National Quality Award (MBNQA) are the two most well-known excellence models. Prior to the Covid-19 outbreak, there was no significant crisis within a decade that put those business excellence principles to the test. This paper looks for a conceptual framework that connects business excellence dimensions and performance with business resilience as a mediator. In this study, three concepts—business excellence, business resilience, and business performance—are conceptually linked. This paradigm should be empirically evaluated in the Qatari companies and looked at from various cultures and markets in order to do more research.